Complete (1)H resonance assignment of beta-maltose from (1)H-(1)H DQ-SQ CRAMPS and (1)H (DQ-DUMBO)-(13)C SQ refocused INEPT 2D solid-state NMR spectra and first principles GIPAW calculations. - Webber, A; Elena, B; Griffin, J; Yates, JR; Pham, T; Mauri, F; Pickard, C; Gil, A; Stein, R; Lesage, A; Emsley, L; Brown, S (2010)
A disaccharide is a challenging case for high-resolution (1)H solid-state NMR because of the 24 distinct protons (14 aliphatic and 10 OH) having (1)H chemical shifts that all fall within a narrow range of approximately 3 to 7 ppm. High-resolution (1)H (500 MHz) double-quantum (DQ) combined rotation and multiple pulse sequence (CRAMPS) solid-state NMR spectra of beta-maltose monohydrate are presented. (1)H-(1)H DQ-SQ CRAMPS spectra are presented together with (1)H (DQ)-(13)C correlation spectra obtained with a new pulse sequence that correlates a high-resolution (1)H DQ dimension with a (13)C single quantum (SQ) dimension using the refocused INEPT pulse-sequence element to transfer magnetization via one-bond (13)C-(1)H J couplings. Compared to the observation of only a single broad peak in a (1)H DQ spectrum recorded at 30 kHz magic-angle spinning (MAS), the use of DUMBO (1)H homonuclear decoupling in the (1)H DQ CRAMPS experiment allows the resolution of distinct DQ correlation peaks which, in combination with first-principles chemical shift calculations based on the GIPAW (Gauge Including Projector Augmented Waves) plane-wave pseudopotential approach, enables the assignment of the (1)H resonances to the 24 distinct protons. We believe this to be the first experimental solid-state NMR determination of the hydroxyl OH (1)H chemical shifts for a simple sugar. Variable-temperature (1)H-(1)H DQ CRAMPS spectra reveal small increases in the (1)H chemical shifts of the OH resonances upon decreasing the temperature from 348 K to 248 K.